Product Placement in Anime: The Impact of Anime Character Associations on Audience Perceptions and Purchasing Intentions - Haryo, Muhammad Ra’if; Alfarisy , Edon Salman (APPS Publications, 2024)
Objective This study delves into the analysis of product placement strategies, examining the impact of character variables on audience perceptions in selected anime works. The primary objective is to ascertain the influence of product placement on audience purchasing intentions, thereby contributing valuable insights to the realms of marketing and advertising literature. Methodology This research uses a quantitative approach with descriptive and causal research types. Primary data was collected by distributing questionnaires; then, the data was processed using Smart-PLS. The population of this study is 100 anime movie/video viewers. Findings The results showed that product placement and attitude toward anime characters positively and significantly affect propensity to acquire the showcased items in anime showing. Novelty This research offers a unique contribution by examining a specific genre (anime), focusing specifically on product placement in anime, and delving into the nuances of character variable and their influence on audience behavior.